Integrating National Character Values through Scouting Education: An Ideal Strategy in the Modern Era - Sasongko, Sempu Dwi; Waryanti, Endang (Asa Jurnal Penelitian Pendidikan dan Pembelajaran, 2025)
Character education is the process of inheriting culture to shape the personality of the younger generation. The world of technology is experiencing rapid development, and the world of education is experiencing many changes due to the advancement of technology. However, there are negative and positive sides to technological advancement. The enormous influence of technology also affects the character of the nation. Therefore, it is important to provide a filter against the negative impact of technology. One of the activities that can be done to filter out the negatives of technological advances is Scouting activities. Scouting, as an informal activity, can be an effective means to instill character values because it has pillars that are relevant to everyday life. In Scouting, young people are taught to have responsibility, discipline, and love for the country. In addition, this activity also encourages character building through activities that involve cooperation, leadership, and social care. This research, through a literature study, analyzed information from various sources and found that Scouting is a suitable platform for instilling National Culture and Character Education. However, Scouting is not the only solution.